ANALYSIS OF THE CONTRIBUTION OF REGIONAL RETRIBUTION TO THE LOCALLY GENERATED REVENUE OF PALEMBANG CITY - Martini, Rita; Pambudi, Septian Bagus; Mubarok, M. Husni (Publikasi Penelitian Terapan dan Kebijakan, 2019)
This study aims to determine the contribution of local retribution to Local Revenue (PAD), and the achievement of the target of each type of regional retribution. The analytical tool used is the contribution ratio and effectiveness ratio. Contribution ratio analysis is used to determine the amount of contribution of local retribution to PAD. The conclusions obtained, the local retribution in Palembang which are carried out according to regional regulations have decreased the realization each year, while the effectiveness level has fluctuated. Local retribution have not contributed to an increase every year, because of changes in the object of retribution, lack of socialization regarding Regional Regulations, and the existence of new types of retribution that have been applied. Specific Licensing Services retribution contribute the most to PAD compared to other types of retribution.